(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This study examines the role of AI tools in shaping students’ study habits and academic outcomes, focusing on their integration into educational routines. A mixed-methods approach was employed, combining survey data and qualitative feedback from 141 students across diverse demographics and disciplines. Key findings reveal a moderate level of AI usage, with 57% of students utilizing AI tools for 26-50% of their study time. AI tools were reported to enhance efficiency, motivation, and GPA while reducing study hours. Despite these benefits, challenges such as over-reliance and integration with traditional methods were identified. The study underscores the importance of a balanced approach to AI adoption, advocating for its role as a complementary tool alongside conventional study practices. Actionable recommendations include promoting responsible usage, addressing privacy concerns, and fostering inclusivity to maximize AI’s educational potential.